1999
DOI: 10.1590/s0004-27491999000600006
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in ocular pathogen susceptibility to gentamicin and tobramycin

Abstract: Alterations in ocular pathogen susceptibility to gentamicin and tobramycinPurpose: To evaluate and compare the "in vitro" susceptibility of ocular bacterial isolates to aminoglycoside antibiotics (gentamicin and tobramycin) and to analyze the alteration in susceptibility after 14 years of introduction of tobramycin in Brazilian ophthalmic practice.Methods: The results of antibiotic susceptibility tests in a period of three years with 887 bacterial strains (Study "A") were retrospectively analyzed and then comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…As in previous studies, many of our cultures showed no microbial growth. There are several possible explanations for this finding, including insufficient material, the use of topical antibiotics before cultures could be inoculated, viral etiology, or the presence of microorganisms that do not grow in regular media, such as anaerobic bacteria or Mycobacteria (19)(20)31) . Some antimicrobial drugs are subject to restricted use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As in previous studies, many of our cultures showed no microbial growth. There are several possible explanations for this finding, including insufficient material, the use of topical antibiotics before cultures could be inoculated, viral etiology, or the presence of microorganisms that do not grow in regular media, such as anaerobic bacteria or Mycobacteria (19)(20)31) . Some antimicrobial drugs are subject to restricted use.…”
Section: Discussionmentioning
confidence: 99%
“…The samples for microbiological evaluation were obtained directly from the infected area in all cases of conjunctival infections. Sterile cotton swabs soaked in BrainHeart-Infusion solution were used for collection of samples for cultures (18)(19) . All the materials were inoculated onto sheep blood agar, chocolate agar, and Sabouraud dextrose agar (5,20) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation